Effect of diet on the human large intestinal microbiota - Simões, Catarina D. (2015)
The impact of diet on the gastrointestinal microbiota has been discussed for several decades. However, advances in molecular microbiological techniques have expanded the knowledge on microbial ecology and the study of the effect of diet and dietary changes on the resident microbiota. It has become evident that diet influences the composition of the microbiota. This review aims to present an overview of the dietary effects on the human fecal microbiota.